Study on workability and strength of fresh and hardened concrete containing various percentage of chipboard waste - Mohd Zulkifli, Mohd Nor (2012)
Nowadays, natural raw materials such as aggregate become more limited. It can be outlined that, the need for other materials from the waste industrial product as an alternative material to replace the natural materials in the concrete. It is an opportunity to study the effectiveness of waste industrial products as aggregate replacement. The use of chipboard waste as the replacement in concrete is one of the alternatives and also environmental friendly. The objectives of this study are to determine the workability of fresh concrete, compressive strength and the splitting tensile strength of hardened concrete. In this study, the mixed of concrete used in this research is for grade 35 N/mm2 and the water/cement ratio is 0.53. 36 numbers of cubes and 12 numbers of cylinder sample is prepared. Four different mix proportions of 0%, 5%, 15% and 25% by weight of chipboard was designated as Sample A, Sample B, Sample C and Sample D respectively. Concrete containing chipboard were classifies as medium workability. The compressive strength of concrete containing 0 %, 5 %, 15 % and 25 % of chipboard waste were 29.82 N/mm2, 27.17 N/mm2, 16.35 N/mm2 and 6.51 N/mm2 respectively and the tensile strength were 2.73 N/mm2 , 2.48 N/mm2 , 1.56 N/mm2 and 0.94 N/mm2 at age of28 days.